2022
DOI: 10.1017/dmp.2022.22
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Relation of Coping Skills with Mental Health and Quality of Life in Family Members of Nurses During the COVID-19 Pandemic

Abstract: Objectives: During the coronavirus disease (COVID-19) pandemic, health care workers, including nurses and their family members, experienced various psychological problems. Coping skills may help them deal with the current challenge and maintain their mental health and improve their quality of life. Therefore, this study investigated the relation of coping skills with mental health and quality of life of the nurses’ family members during the COVID-19 pandemic. Methods: This cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 28 publications
0
10
1
Order By: Relevance
“…There is inconsistency between the studies regarding the age or relationship with the hospital staff, perhaps due to the difference in the distribution of subject demographics or survey period from the beginning of COVID-19 pandemic. Moreover, there was a relatively small number of samples in our study compared with previous studies, 12,13 potentially leading to beta error regarding association between psychological problems and risk factors.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…There is inconsistency between the studies regarding the age or relationship with the hospital staff, perhaps due to the difference in the distribution of subject demographics or survey period from the beginning of COVID-19 pandemic. Moreover, there was a relatively small number of samples in our study compared with previous studies, 12,13 potentially leading to beta error regarding association between psychological problems and risk factors.…”
Section: Discussionmentioning
confidence: 84%
“…A previous study conducted a questionnaire survey of families of COVID‐19 frontline nurses. Mild, moderate, or severe depression in their subjects were reported as 22.6%, 71.4%, and 1.8%, respectively 13 . Another study on depression and anxiety of family members of hospital staff involved in frontline care of patients with COVID‐19 reported that 29.4% of the subjects had depression and that 33.7% of the subjects had anxiety 12 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations